2004
DOI: 10.1002/ptr.1512
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen activation by photoexcited protoberberinium alkaloids from Mahonia aquifolium

Abstract: Protoberberinium salts, i.e. berberine (I), palmatine (II) and jatrorrhizine (III) prepared from Mahonia aquifolium (Pursh) Nutt. belong to isoquinoline alkaloids possessing interesting biological activity (e.g. antibacterial, antimalarial, antitumor). The characteristic UV/Vis absorption band maxima of I-III iodide salts were found in regions 350 and 425 nm in dimethylsulfoxide (DMSO) and ethanol solvents, and were only negligibly influenced by substitution changes on the C-2 and C-3 positions. The fluorescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 53 publications
0
13
1
Order By: Relevance
“…Methyl-hernovine was detected for the first time in G. flavum and columbamine in B. thunbergii . According to literature data, columbamine occurs in C. cava [ 24 ] and M. aquifolium [ 25 ] which was not confirmed in this study. Methyl-corypalmine was detected in F. officinalis for the first time.…”
Section: Resultscontrasting
confidence: 89%
See 1 more Smart Citation
“…Methyl-hernovine was detected for the first time in G. flavum and columbamine in B. thunbergii . According to literature data, columbamine occurs in C. cava [ 24 ] and M. aquifolium [ 25 ] which was not confirmed in this study. Methyl-corypalmine was detected in F. officinalis for the first time.…”
Section: Resultscontrasting
confidence: 89%
“…In this study, the presence of fumarophycine [ 26 ] and corydamine [ 27 ] in this plant material was confirmed. The presence of jatrorrhizine in M. aquifolium [ 25 ] and corydaline in C. cava [ 28 , 29 ] was also confirmed, but not in F. officinalis [ 27 ]. Corydine and tetrahydropalmatine were found in this study only in C. cava but were not in other investigated plant species.…”
Section: Resultsmentioning
confidence: 99%
“…Alkaloids are photosensitive molecules that can induce the production of superoxide and singlet oxygen upon irradiation in the UVA region (Hudson & Towers, 1991; Brezova et al ., 2004). Although artificial light sources emitting UVA were not used in our experiment, we found that a variety of superoxide‐inducible genes were upregulated by BC (Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…Various isoquinoline alkaloids are used as traditional medicines in the Orient because of their immunomodulatory, antiinflammatory and antibacterial effects (Brezová et al, 2004;Jantan et al, 2006). In addition, they decrease the activity of elastase reductions in which are known to be associated with inflammatory disease and the development of arthritis (Tanaka et al, 1993).…”
Section: Introductionmentioning
confidence: 99%